2003
DOI: 10.1021/jp0208790
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in the Autoxidation of S(IV) Inhibited by Phenolic Compounds

Abstract: The effects of phenol (C6H5OH), catechin [C6H4(OH)2], and gallic acid [HOOCC6H2(OH)3] on the kinetics of aqueous SO2 oxidation by molecular oxygen have been investigated for dilute systems, as pertain to the chemistry of troposphere and surface waters. In experiments performed under batch (homogeneous oxidation) or semibatch (heterogeneous oxidation) conditions, we measured the decay of oxygen with a Yellow Spring Instruments probe or the increase in S(VI) concentration with an Orion conductivity cell. All of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The rate law (6) for the inhibition is same as reported by Alyea and Backstrom [27], Pasiuk-Bronikowska et al [9], Manoj et al [26] and Mudgal et al [29] for inhibition of sulfur(IV) autoxidation with different types of inhibitors. To explain the inhibition, the operation of a radical mechanism [3,11,13] involving oxysulfur radicals, viz., SO 3 -, SO 5 -, SO 4 -has been proposed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The rate law (6) for the inhibition is same as reported by Alyea and Backstrom [27], Pasiuk-Bronikowska et al [9], Manoj et al [26] and Mudgal et al [29] for inhibition of sulfur(IV) autoxidation with different types of inhibitors. To explain the inhibition, the operation of a radical mechanism [3,11,13] involving oxysulfur radicals, viz., SO 3 -, SO 5 -, SO 4 -has been proposed.…”
Section: Discussionmentioning
confidence: 56%
“…The reaction has been studied [1][2][3][4][5][6][7][8][9][10] repeatedly and reviewed extensively [11][12][13][14][15][16][17][18]. However, most of the detailed studies pertain to low pH region (0-3) in which the kinetics obeys the rate law (1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For this reaction both radical and non-radical mechanisms have been proposed [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent and a more detailed study on the inhibition of S(IV) autoxidation by VOCs, most of which comprise aliphatic compounds, Dhayal et al [31] found the following relationship between k inh and B. www.prkm.co.uk B = (9 ± 2) × 10 −4 k inh (17) For uncatalysed S(IV) autoxidation, in general, the ratio k inh /B is about 10 3 . Accordingly, based on k inh values of 4.9 × 10 9 -7.2 × 10 9 L mol -1 s -1 for methoxybenzenes, the B values are expected to be about 10 6 L mol −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, reaction (8) acts as a sink for the oxidation and removal of VOCs from the atmosphere. There are many studies on the chemistry of the reaction VOCs → sulfate radical anion and its inhibition kinetics [6,[12][13][14][15][16][17][18][21][22][23][24][25][30][31], which follows the rate law…”
Section: Terminationmentioning
confidence: 99%
“…This led us to look afresh into the atmospheric chemistry of H 2 S oxidation and to examine the effect of several parameters such as reactant concentrations, pH and importantly the effect of some anthropogenic volatile organic compounds(VOCs) particularly those which are reported to strongly inhibit the oxidation of aqueous SO 2 by oxygen in laboratory water. The oxidation kinetics of aqueous SO 2 and effect of VOCs has been studied by several groups [3,8,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] .…”
Section: Introductionmentioning
confidence: 99%